EVALUATION OF DIPHTHERIA SURVEILLANCE SYSTEM IN PROBOLINGGO DISTRICT: STUDY OF SYSTEM APPROACH AND ATTRIBUTES: Evaluasi Sistem Surveilans Difteri di Kabupaten Probolinggo: Studi Pendekatan Sistem dan Atribut - Nur Maulina, Lidya; Novita Sari, Siti Shofiya; Tarawally, Abubakar; Sholikah, Sholikah; Anjar, Retno (Jurnal Berkala Epidemiologi, 2025)
Background: There is still an outbreak of diphtheria in the Probolinggo district in 2023. Diphtheria mainly affects children who are not immunized. Support through a surveillance system is needed to overcome the diphtheria problem. Purpose: This study aims to describe the quality of diphtheria surveillance systems based on system approach and surveillance attributes. Methods: Descriptive research was carried out on 17 samples with an evaluation study on the diphtheria surveillance system in 2023 at health centers in the working area of the Probolinggo District Health Office. Data were collected by interview and document study using questionnaires and check list sheets. Data analysis was carried out by describing the system components and attributes of the surveillance system in 17 respondents, compared with the Diphtheria control guideline book 2023, Indonesian Minister of Health Regulation No. 45 of 2014, and surveillance attributes from CDC. The information obtained was presented in the form of tables and narratives. Results: The evaluation of diphtheria surveillance system components (input, process, output) in Probolinggo District was done using surveillance guidelines. Meanwhile, the diphtheria surveillance system assessment based on attributes showed simplicity, flexibility, acceptability, representativeness, stability, and good data quality. However, the system is not yet sensitive, and timeliness is still low. Conclusion: The implementation of the diphtheria surveillance system has mainly been carried out well, supported by the completeness of several surveillance attributes. Optimizing the use of the  Early Warning and Response System (EWS) application is necessary to improve the current surveillance system.